ZnO And MoSexOy Modified TiO2 Nanotubes For Photoelectrochemical And Sensing Applications - Ng, Siow Woon (2018)
One-dimensional (1D) anodic self-organized TiO2 nanotube layers have attracted considerable scientific and technological interest over a decade. The major drawbacks are their rather wide band gap energies (3.0–3.2 eV) with high photoactivity only in the ultraviolet (UV) spectral region (l 390 nm, 5% of the solar spectrum), relatively low conductivity and high carrier recombination rate. Furthermore, as a high aspect ratio (HAR) nanostructure, the deposition of a uniform secondary coating within the TiO2 nanotube layers remains a challenge. To overcome these critical issues, present work is intended (i) to synthesize anodic 1D TiO2 nanotube layers as an independent semiconductor and for the incorporation of secondary materials; (ii) to produce homogeneous and conformal ZnO and MoSexOy coatings by atomic layer deposition (ALD) within TiO2 nanotube layers; (iii) to form heterostructure in order to enhance charge transport efficiency, increase light absorption and extend the functional range to the visible spectral region; and (iv) to evaluate UV photodetection responses, ethanol sensing responses at low temperatures, photocurrent generation and photocatalytic degradation of methylene blue (MB). The synthesis of the TiO2 nanotube layers was carried out by a conventional electrochemical anodization of Ti sheet in fluorinated organic electrolytes. A low bias, visible-blind, UV photodetector was constructed in a sandwich structure comprising of ITO/electrolyte/TiO2 nanotubes/Ti for the first time to investigate the photodetection in UV-A, B and C spectral regions.